RASIO PREVALENSI ALLOANTIBODI PADA PASIEN TRANSFUSI BERULANG DIBANDING TIDAK BERULANG - , TITIEN BUDHIATY, dr. Teguh Triyono, MKes, SpPK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Allogenic blood transfusion has potential effect to trigger the formation of alloantibody in the recipient due to blood group antigen differences between donor and recipient. Thalassemia, hemodialysis, and malignancies patients get anemic during their illness, therefore requiring repeated and multiple erythrocyte transfusions. This increases the risk of developing alloantibody. Previous studies found that alloantibody incidence varies from 4-60%. The adverse event due to alloantibody is hemolytic transfusion reactions or HDN. The purpose of this study was to determine the prevalence ratio of alloantibody in patients with repeated transfusion compared to non repeated transfusion. This study used cross-sectional design. The study subjects consisted of two groups: patients who received repeated transfusions, consisting of thalassemia, HD, and malignancies and patients who received transfusion only in once episode. A total of 170 subjects were included in this study, each group consisted of 85 subjects. Screening and identification of antibodies were done in both groups. Prevalence ratio is analyzed with chi-square test. Logistic regression is performed to analyze the influence of other factors that contribute to alloantibody formation such as diagnose, number of transfusion and frequency of transfusion. The prevalence ratio of the alloantibody is 8:1. Red cell alloantibody prevalence in the repeated transfusion (9,41%) significant differ statistically than non repeated transfusion (1,17%) (p=0,034). The probabilities of alloantibodies are anti-E, -K, -Kpa, -Cw, -Co(b+) and canât identified ones. No signs of hemolytic transfusion reaction was found. Further study is needed with consider the timing of antibody screen from the last transfusion event, the availability of additional panel cell to identify alloantibody and antisera to confirm specificity of the alloantibody.